Simulation of buckling-driven progressive damage in composite wind turbine blade under extreme wind loads. (October 2022) - Ullah, Himayat; Alam, Khurshid; Iqbal, Muhammad; Husain, Afzal; Silberschmidt, Vadim V.
Highlights: Interactive damage of adhesive joint and composite shell in blade is simulated numerically. Nonlinear finite element analysis revealed local skin buckling on compression side. Buckling driven debonding and composite damage is modelled with cohesive zone model and continuum damage mechanics. Skin-spar joint debonding is the initial damage leading to the blade ultimate failure. Abstract: Wind turbine blades are continuously upscaled in size to meet the increasing demand of low cost renewable energy. The larger and slender blades with reduced mass are susceptible to large-deflection bending and instability during extreme wind gusts. The loading can induce interactive damage modes such as adhesive bond failure and composite skin damage progressively degrading the blade structural performance. The structural deformation and instability as well as progressive damage in composite blade is analyzed by developing finite element (FE) models using ANSYS software. First, a geometric nonlinear FE analysis of the 3D blade is performed to predict its deflection and regions of high stresses. The results demonstrated that high compressive stresses in the blade suction side trigger local skin buckling; thus initiating debonding of weak adhesive interface joint between skin and spar combined with skin damage. Subsequently, the interactive buckling-driven skin-spar debonding and composite skin damage in the identified region are analyzed through a submodel using cohesive zone model (CZM) as well as continuum damage mechanics (CDM) based progressive failure analysis, respectively, through a user-defined material subroutine. The results indicated that buckling-driven debonding of adhesive interface between skin and spar was primary damage mode leading to progressive failure of the blade composite skin. Consequently, the blade ultimate load carrying-ability was governed by coupled adhesive debonding and progressive skin damage phenomena, which is in good agreement with published experimental results. The developed simulation approach is capable to efficiently analyze the interactive buckling-induced interface damage as well as progressive failure of composite blade structure. In this work, modelling of interaction between interface debonding and skin damage, based on the CZM and CDM scheme, is a novel methodology for progressive damage analysis of blade under extreme loading.